THE CHALLENGE DIGITALISATION OF PENSION FUND SERVICES FOR ELDERLY PENSIONERS: EVALUATION OF THE USE OF DAPENBUN ONLINE APPLICATION AT PTPN III MEDAN - Ade Kurnia Sari; wid dia; Annio Indah Lestari Nasution (STIESA Press, 2025)
Digitalisation has been a key driver in the transformation of Indonesia's financial sector and pension services, but elderly retirees face various obstacles, such as low digital literacy, limited internet access, and physical difficulties in using technology. This article discusses the challenges of digitalisation of pension fund services for elderly retirees through an evaluation of the use of the Dapenbun Online application at PTPN III Medan. This research uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation studies. The results show that although the Dapenbun Online application offers easy access to information and pension claims, it still has various challenges. Therefore, this article recommends solutions such as ball pick-up services, development of telephone services, and training to improve technological understanding among retirees, in order to create a more inclusive and responsive service to the needs of elderly retirees.